SOSIALISASI STRATEGI PENGALIHAN RISIKO MELALUI PERENCANAAN DANA ASURANSI SYARIAH PADA PENGEMUDI OJEK ONLINE - Ilda Alfiah; Rafika Rahmawati; Fajri Ryan Isnandar (Universitas Islam 45 Bekasi, 2022)
Currently, there are still many people who cannot distinguish between Sharia Insurance and Conventional Insurance and some even do not know it at all even though insurance is very important for self-protection, especially in the current Pandemic Era. Therefore, this activity is carried out with the aim that the public can better know, understand, trust and apply sharia insurance as a good medium of self-protection. Then this paper was made with another purpose, namely as a report for the 2022 Real Work Lecture (KKN) organized by LPPM Islamic University